Art, Politics, and Development : How Linear Perspective shaped Policies in the Western World. - Lepenies, Philipp H. (Politics History & Social Chan., 2013)
In his groundbreaking study, Art, Politics and Development, Philipp Lepenies contributes to the ongoing controversy about why the track record of development aid is so dismal. He asserts that development aid policies are grounded in a specific way of literally looking at the world. This "worldview" is the result of a mental conditioning that began with the invention of linear perspective in Renaissance art. It not only triggered the emergence of modern science and brought forth our Western notion of progress, but ultimately, development as well. Art, Politics, and Deve.